Metallo-stannosilicate heterogeneous catalyst for biodiesel production using edible, non-edible and waste oils as feedstock - Silva, Danilo Antonio da [UNESP]; Santisteban, Oscar A. N. [UNESP]; Vasconcellos, Adriano de [UNESP]; Paula, Alex Silva [UNESP]; Aranda, Donato A. G.; Giotto, Marcus Vinicius; Jaeger, Christian; Nery, Jose G. [UNESP] (Elsevier B.V., 2018)
This study reports the synthesis, physicochemical characterization by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and solid-state MAS NMR (H-1, Na-23, Si-29 and Sn-119 MAS NMR) of a metallo-stannosilicate and its application as a heterogeneous catalyst for biodiesel production via ethanolysis and methanolysis routes using edible, non-edible an waste oils as feedstocks. XRD characterization of the metallo-stannosilicate has revealed a typical structure of mixed octahedral-pentahedral-tetrahedral material with an orthorhombic unit cell (a = 14.522 angstrom, b = 12.469 angstrom, and c = 10.654 angstrom). Sn-119 single-pulse MAS NMR results presented two resonance lines, at delta(1)= -683.8 ppm and delta(2) = -690.9 ppm, which were assigned to the fin octahedrally coordinated in the metallo-stannosilicate structure. Heterogenous catalytic studies in the transesterification of refined edible, non-edible, and waste oils have resulted in high yields of FAMEs and FAEEs (fatty acid methyl and ethyl esters), nevertheless the highest FAMES (98.2%) and FAEEs (96.6%) yields were obtained for non-edible microalgae oil extracted from the genetically modified heterotrophic algal strain Prototheca moriformis. Catalytic studies also using non-edible macaw palm oil (Acrocomia aculeata) with a high content of free fatty acids (FFAs) demonstrated that the catalyst could simultaneously perform esterification and transesterification reactions. These findings indicate the potential application of this novel metallo-stannosilicate in the production of renewable and environmentally clean biofuels, like biodiesel, using different sources of lipids feedstocks, notably those that do not compete with food production.
Keywords: Sol-gel chemistry; Metallo-stannosilicate; Biofuels; Biomass; Edible and non-edible lipid feedstocks